1998
DOI: 10.1159/000054295
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Regulation of Leptin Receptor Isoforms in the Rat Brain: Effects of Fasting and Oestrogen

Abstract: Leptin affects body weight and reproduction mainly via receptors in the central nervous system. Different isoforms of the leptin receptor (leptin-R) exist, including a long isoform (leptin-RL) with signalling capacity and short isoforms (leptin-RS) with unknown function. The aim of this study was to examine leptin-R gene expression in different regions of the brain under conditions with altered body weight, in the female rat, including ovariectomy (OVX), oestradiol (E2) treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
5
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 37 publications
(70 reference statements)
5
69
5
2
Order By: Relevance
“…The disparity may be resolved when such studies are conducted in controlled artificial photoperiods rather than in natural photoperiods. Nonetheless, unlike in the present study, the sheep used by Clarke et al (2001) did not have gonadal steroid replacement and it is suggested that oestradiol is required to facilitate leptin actions in the brain (Bennett et al 1998, Pelleymounter et al 1999, Ainslie et al 2001, Kimura et al 2002. Photoperiodic modulation of leptin-induced body weight (or fat) loss is seen in the Siberian hamster, with sensitivity to leptin in two separate studies found to be greatest in a short-as opposed to a long-day photoperiod (Atcha et al 2000.…”
Section: Discussioncontrasting
confidence: 51%
“…The disparity may be resolved when such studies are conducted in controlled artificial photoperiods rather than in natural photoperiods. Nonetheless, unlike in the present study, the sheep used by Clarke et al (2001) did not have gonadal steroid replacement and it is suggested that oestradiol is required to facilitate leptin actions in the brain (Bennett et al 1998, Pelleymounter et al 1999, Ainslie et al 2001, Kimura et al 2002. Photoperiodic modulation of leptin-induced body weight (or fat) loss is seen in the Siberian hamster, with sensitivity to leptin in two separate studies found to be greatest in a short-as opposed to a long-day photoperiod (Atcha et al 2000.…”
Section: Discussioncontrasting
confidence: 51%
“…These findings indicate that the blunted GH responses to GHRH induced by food deprivation reflect a functional and reversible state, and suggest that the primary alteration could be mediated by decreased leptin activation of the hypothalamic-GH axis. It is also possible that the effect of leptin in food-deprived rats could be the result of increased gene expression of the long isoform of the leptin receptor in the hypothalamus, in response to fasting (36). However, this stimulatory effect of leptin on GH responses to GHRH resembles that obtained by others who assessed the same response after passive immunization with antisomatostatin antiserum (31).…”
Section: Discussionmentioning
confidence: 91%
“…Several studies suggested that the estrogen and leptin systems are related via functional cross talk. For example, estrogens have been shown to regulate the expression of leptin (Casabiell et al, 1998;Tsuruta et al, 2004) and its receptor (Bennett et al, 1998) in adipose tissue and brain, respectively. Reciprocally, leptin stimulates ovarian cancer cell growth involving ERα transcriptional activation via the STAT-3 signaling pathways (Choi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%